Rheological properties of binary mixtures of Lepidium perfoliatum seed gum and xanthan gum - Alireza Yousefi; Komla Ako; Ghader Hosseinzadeh; Shahla Khodabakhshaghdam (Chemical and Biological Technologies in Agriculture, 2023)
Abstract Background In this work, viscoelasticity, flow behaviour, thixotropy and thermo-rheological properties of binary mixtures of Lepidium perfoliatum seed gum (LPSG), as an emerging food gum, and xanthan gum (XG) at various blending ratios of 100:0, 75:25, 50:50, 25:75 and 0:100 were studied for a depth insight into their interaction. FTIR analyses were also done to investigate the interaction between the XG and LPSG. Results FTIR results indicated the hydrogen bond formation between the hydrocolloids. At the linear viscoelastic region (LVE), XG-rich blends exhibited higher tan δ LVE and τ y , but lower τ f . The values of apparent viscosity (η a ) and complex viscosity (η * ) diminished with increasing shear rate/frequency, and XG and LPSG individual dispersions showed the greatest and the lowest values, respectively. Based on the extended Cox-Merz rule, a greater shift factor (α) is observed as the ratio of LPSG in the mixed gel increases. At higher fraction of LPSG, except for the fraction of 75%, the thixotropic behaviour appears to be less pronounced. The recovery parameter (R, %) obtained from in-shear structural recovery test decreased with increase in LPSG fraction. The results of non-isothermal kinetic analysis revealed higher thermodynamic incompatibility and immiscibility of LPSG-XG system in the presence of 75% XG. Moreover, according to the results of Cole–Cole plot, the greatest compatibility of LPSG and XG blends was for LPSG75-XG25 sample (β = 0.87), whereas the worst miscibility was found to be for LPSG25-XG75 one (β = 1.02). Conclusions Different rheological properties could be obtained by blending various ratios of LPSG and XG, which in some ratios synergistic behaviour was observed. The wide variety of rheological properties obtained may be appropriate for the use of LPSG-XG mixtures in food industries and pharmaceutical and biomedical applications. Graphical Abstract